Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Entity Disambiguation and the Role of Popularity in Retrieval-Based NLP

Abstract: Retrieval is a core component for open-domain NLP tasks. In open-domain tasks, multiple entities can share a name, making disambiguation an inherent yet under-explored problem. We propose an evaluation benchmark for assessing the entity disambiguation capabilities of these retrievers, which we call Ambiguous Entity Retrieval (AmbER) sets. We define an AmbER set as a collection of entities that share a name along with queries about those entities. By covering the set of entities for polysemous names, AmbER sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 33 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…L type (Q) uses type labels to form positive and negative pairs over queries. 6 Let P type (q) be the set of all queries in a batch that share the same type t as a query q and N type (q) be the other queries in the batch with a different type. Then L type (Q) is:…”
Section: Type-enforced Contrastive Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…L type (Q) uses type labels to form positive and negative pairs over queries. 6 Let P type (q) be the set of all queries in a batch that share the same type t as a query q and N type (q) be the other queries in the batch with a different type. Then L type (Q) is:…”
Section: Type-enforced Contrastive Lossmentioning
confidence: 99%
“…Retrieving the correct George Washington in the query above-George Washington the baseball player, rather than George Washington the president-requires the retriever to recognize that keywords "team" and "play" imply George Washington is an athlete. However, recent work has shown that state-ofthe-art retrievers exhibit popularity biases and struggle to resolve ambiguous mentions of rare "tail" entities [6].…”
Section: Introductionmentioning
confidence: 99%
“…The framework maps a QA instance x = (q, a, c), with query q, answer a, and the context passage c in which a appears, to x = (q, a , c ) where a is replaced by substitution answer a as the gold answer, and where all occurrences of a in c have been replaced with a , producing new context c . This substitution framework extends partiallyautomated dataset creation techniques introduced by Chen et al (2021) for Ambiguous Entity Retrieval (AmbER). Our dataset derivation follows two steps: (1) identifying QA instances with named entity answers, and (2) replacing all occurrences of the answer in the context with a substituted entity, effectively changing the answer.…”
Section: Substitution Frameworkmentioning
confidence: 99%
“…How does Popularity of an Answer Entity impact Memorization? Using popularity substitution we examine if models are biased towards predicting more popular answers (Shwartz et al, 2020;Chen et al, 2021). Limiting our focus to the Person answer category, we order all PER Wikidata entities by popularity (approximated by Wikipedia monthly page views) and stratify them into five evenly sized popularity buckets.…”
Section: How Doesmentioning
confidence: 99%
“…WikiDisamb30 (Ferragina and Scaiella, 2012), ACE and MSNBC (Ratinov et al, 2011), WNED-CWEB and WNED-WIKI (Guo and Barbosa, 2018) CoNLL-YAGO (Hoffart et al, 2011), and TAC KBP Entity Discovery and Linking dataset (Ji et al, 2017). The recently introduced Ambiguous Entity Retrieval (AmbER) dataset by Chen et al (2021) is an exception, including subsets of identically named entities for the purpose of fact checking, slot filling, and question-answering tasks. AmBer is limited to Wikipedia text and was automatically generated.…”
Section: Introductionmentioning
confidence: 99%